Sociodemographic Factors and Depressive Symptoms Among Cardiac Nurses: A Cross-Sectional Study - Larysz, Anna; Uchmanowicz, Izabella (Frontiers in Psychology, 2021)
Background. The nursing profession is predisposed towards depressed mood and depressive symptoms. The multidirectionality and intensity of stressors in the nurses' occupational environment are of great significance in this respect. The study aimed to evaluate the impact of selected sociodemographic factors on depressive symptoms among cardiac nurses. Methods. This cross-sectional study included 336 cardiac nurses (302 women and 34 men) and was conducted between December 2019 and September 2020 in four hospital cardiac units in Wroclaw, Poland. Sociodemographic data were collected using a self-developed survey. The following standardized instruments were used for the study outcomes: Patient Health Questionnaire-9 (PHQ-9) and Beck Depression Inventory (BDI). Results. The study among cardiac nurses showed mild depression in 11.61%, moderate depression in 5.06%, and severe depression in 2.68%. Linear regression models showed that significant (p˂0.05) predictors of the PHQ-9 score included (1) higher occupational education (bachelor’s degree), graduation "only" from medical high school or "other" education; (2) work experience of 16-20 years; (3) living in a relationship; (4) living in a rural area. Linear regression models showed that significant (p˂0.05) predictors of the BDI score included (1) higher occupational education (bachelor's degree); (2) graduation "only" from medical high school or "other" education; (3) living in a relationship. Conclusions. Depressive symptoms are a significant problem among Polish cardiac nurses. The prevalence of depressive symptoms is affected by the education level, employment form, marital status, and place of residence.